KAJIAN POLA PEMENUHAN NUTRISI DAN HIDRASI IBU BERSALIN SELAMA PROSES PERSALINAN - Saleh, Ummi Kaltsum S.; Namangdjabar, Odi L.; Saleh, Asmulyati S. (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2021)
Labor is a physiological process that requires energy and endurance. Fulfillment of nutrition and hydration are important factors during the labor process to ensure adequate energy and normal fluid and electrolyte balance in the mother. Normal delivery care recommends providing nutritional intake to pregnant women, but so far the nutritional needs of mothers have not been taken into account so that it is not known whether the nutritional needs of mothers have been fulfilled or not. Ideal food for pregnant women must have homogeneous quality, liquid or semi-solid, contain iso osmotic, neutral pH, neutral temperature, high in carbohydrates, high in calories, low in fat, low in residue and delicious. Objective: This study aims to determine the fulfillment of nutrition and hydration of pregnant women during the delivery process at the Sikumana Health Center. This study was a descriptive study with a survey method approach to identify the type and amount of nutrition intake and hydration of pregnant women during the 1st, 2nd, 3rd and 4th stages of labor. The results showed that the foods consumed by the mother during labor were rice, vegetables, and side dishes. While for the drinks consumed are water and tea. The provision of information about the importance of fulfilling hydration (eating and drinking) to mothers since pregnancy is highly recommended so that the knowledge and understanding of mothers in childbirth is good.